2011
DOI: 10.1103/physrevlett.106.176401
|View full text |Cite
|
Sign up to set email alerts
|

Polariton Condensation in a One-Dimensional Disordered Potential

Abstract: We study the coherence and density modulation of a nonequilibrium exciton-polariton condensate in a one-dimensional valley with disorder. By means of interferometric measurements we evidence a modulation of the first-order coherence function and we relate it to a disorder-induced modulation of the condensate density, that increases as the pump power is increased. The nonmonotonic spatial coherence function is found to be the result of the strong nonequilibrium character of the one-dimensional system, in the pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
36
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 26 publications
2
36
0
Order By: Relevance
“…This strain may be relieved via dislocations which form a characteristic crosshatch pattern. 8 Disorder in microcavities strongly modulates the potential experienced by polaritons through the photonic component and may result in partial 9 or even total polariton confinement. 10 Similarly, the Rabi splitting exhibited by a microcavity is dependent upon the number and the confinement energy (depth) and hence exciton oscillator strength of the QWs.…”
mentioning
confidence: 99%
“…This strain may be relieved via dislocations which form a characteristic crosshatch pattern. 8 Disorder in microcavities strongly modulates the potential experienced by polaritons through the photonic component and may result in partial 9 or even total polariton confinement. 10 Similarly, the Rabi splitting exhibited by a microcavity is dependent upon the number and the confinement energy (depth) and hence exciton oscillator strength of the QWs.…”
mentioning
confidence: 99%
“…It is interesting that, in contrast to the experimentally reported algebraic decay in 2D polariton systems [15,36], the spatial coherence function of a one dimensional condensate is indicated to reach a constant plateau at large distances [16,37,38]. However, in these reports the clarity of this behavior is either obscured by large experimental errors resulting from the applied double slit technique [38] or by strong oscillations in the correlation function related to inhomogeneities of the 1D trap [16] and a comparably short long-range order in the range of 10 μm [37]. For the purposes of assessing the long-range coherence behavior, the 1D polariton condensate in our experiments may roughly be characterized as a finite area but uniform 1D condensate due to its smooth steady-state profile.…”
mentioning
confidence: 77%
“…In particular, polariton condensation in one dimensional channels has drawn special attention. It was demonstrated that polaritons trapped in a channel reveal the appearance of ODLRO in the condensation regime [16]. Moreover, the droplets of BECs in such systems can propagate over macroscopic distances, preserving their coherence properties and allowing for the efficient manipulation [17].…”
mentioning
confidence: 99%
“…Only recently, polariton condensation was experimentally confirmed [4] and it paved the way to the study of many collective quantum phenomena in semiconductor microcavities, such as superfluid properties [5][6][7][8][9][10], or macroscopic phase coherence [11][12][13][14][15]. Many of these results were obtained after quasi-resonant excitation at the inflection point of the lower polariton branch (LPB), in the so-called optical parametric oscillator (OPO) configuration.…”
Section: Introductionmentioning
confidence: 99%